Optical properties of edge-linked polymer porphyrin LB films - Grieve, M; Richardson, T; Anderson, H; Bradley, D (1996)
An investigation of the optical properties of a novel porphyrin molecule which is edge-linked via acetylenic sidegroups to form a highly conjugated molecular system has been performed. Langmuir and Langmuir-Blodgett (LB) films of this material have been prepared and found to form highly ordered monolayers. UV-Vis absorption spectroscopy has been used to study the optical absorption of the polymer in solution, LB monolayer and multilayer form. Linear dichroism has been measured for films deposited at 12 and 39 mN m-1 in order to probe the influence of surface pressure on the orientation of the polymer backbone with respect to the withdrawal direction (deposition axis). An in-plane isotropic polymer backbone distribution is observed for a monolayer deposited at low pressure, but the polymer chains are seen to gradually align in a direction parallel to the withdrawal direction as the number of transferred layers increases indicating the aligning role played by the first few deposited porphyrin monolayers. The degree of alignment can be accelerated when the deposition speed is increased. The linear dichroism of mixed LB films (polymer porphyrin/tricosanoic acid) deposited at high surface pressure indicates that the alignment of the polymer backbone is dictated by the compression geometry of the Langmuir trough in that the polymer chains align orthogonally to the deposition axis when the compression barrier is parallel to plane of the substrate.